Analysis of Large-Scale Privatisation in the Czech Republic in the Years 1991-2005 on the Sample of Selected Privatised Companies - Karel Havlíček; Ivana Turková; Gabriela Dlasková (Entrepreneurial Business and Economics Review)
The objective of this paper is to analyse, evaluate and compare the individual methods of Czechoslovak and Czech privatisation in the years 1991-2005 based on long-term economic indicators. The empirical research focuses on a sample of 60 companies privatised between 1991 and 2005 which were selected from the list of 3500 large-scale privatised firms in the Czech Republic by the National Property Fund of the Czech Republic and divided into three groups.